Methylocystis parvus: genomics, engineering and sustainable PHB production - Claxton Stevens, Benedict H. (2024)
Methylocystis parvus OBBP is a gram-negative aerobic methanotroph of the phylum Alphaproteobacteria. The type species of its genus and type strain of its species. Methanotrophs are industrially relevant organisms defined by their ability to use methane as their sole carbon and energy source. Among many qualities M. parvus is capable of the production of poly(3-hydroxybutyrate) (PHB) which is biodegradable and if produced from biogas, is a bioplastic meaning it is produced from renewable biomass. PHB produced by methanotrophs thus has the potential to aid in the current climate crises of plastic waste and greenhouse gas emission fitting into a circular carbon economy.